Phylogeny of Holothuria leucospilota (Echinodermata: Holothuroidea)as inferred from cytochrome c oxidase I mtDNA gene sequences - Idris, Mohd Yaman; Ahmad, Hajar Fauzan; Hashim, Ridzwan; Usup, Gires; Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah (Faculty of Resource Science and Technology, Universiti Malaysia Sarawak, 2011)
This study aimed to generate the genetic profile of Holothuria (Mertensiothuria) leucospilota (Brandt 1835) from Intan Besar Island, Langkawi, Kedah Darul Aman, Malaysia and then to determine the phylogenetic relationship between H. leucospilota and other members of genus Holothuria available in the GenBank using partial sequences of cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene. In this study, tree topologies of neighbour joining, maximum parsimony and maximum likelihood show that H. leucospilota has its own monophyletic clade clearly distinct from the other species and it is genetically closer to Holothuria (Acanthotrapeza) coluber Semper 1868.